INCULCATING THE VALUES OF NATIONALISM THROUGH HISTORICAL LEARNING IN SMA NEGERI 1 PAJANGAN - Gandhi Ramadhan; Ayu Niza Machfauzia (ISTORIA: Jurnal Pendidikan dan Sejarah, 2018)
ABSTRACT This research aimed to (1) describe the effort to inculcate the values of nationalism in school; (2) describe efforts to inculcate the values of nationalism in the history learning; (3) identify the obstacles of history teacher in instilling the values of nationalism. This research was a naturalistic qualitative research. The sample was determined through purposive sampling and snowball sampling. The data were collected through observation, interviews, and documentation. The data trustworthiness was done through triangulation. Interactive model of Miles and Huberman were used for data analyzed. The results of the research showed that (1) the efforts to inculcate the values of nationalism in SMA Negeri 1 Pajangan had been implemented through the policy and school order. The suspension system became the basis for disciplining learners in school; (2) the inculcation of the values of nationalism by the history teacher was done through preparation of the lesson planing, teaching media according to material, lecturing method and discussion; (3) there were three factors that became obstacles of history teacher in the effort to inculcate the values of nationalism, were a) history teacher, b) attitudes of learners, and c) learning facilities. Keywords: the cultivation of the values of nationalism, nationalism, the study of history.